AN ECONOMIC ANALYSIS OF THE COMPETITIVENESS OF DATES AND THEIR ROLE IN INTERNATIONAL AGRICULTURAL MARKETING IN IRAQ FOR THE PERIOD 2005-2019 - R.T. Al-Wasity; A. F. Ahmed; S. A. Albadawi (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2023)
The development of exports in an open economic environment is the best solution in accelerating the pace of economic growth. The research evaluates the competitiveness of Iraqi dates exports based on a set of quantitative indicators and shows the role of Trade activities represented by international marketing that ensures the flow of goods and services from production until they reach the consumer. The research found a competitive advantage for Iraq in its exports of dates, as the Revealed Comparative Advantage - RCA showed a remarkable rise during the years of study and reached 26.98 in 2008, as for the Concentration Index (H), which represents the concentration of exports in a product or a limited number of products. More than 0.5 came in all the years of the study and it reached 0.91 in 2010. That means, the concentration of Iraqi agricultural exports with a large percentage in dates exports, which means placing agricultural exports and the agricultural trade balance in a difficult position if crop production is exposed to shocks that affect the quality and quantity of production, such as epidemic pests, bad weather or price disturbances in global markets. The research recommended using the comparative advantage that distinguishes Iraq in the production of dates and working to increase the market share by finding new marketing channels.